Notes to Philosophy 167: Class 3 -- Kepler's Astronomia Nova: The Orbit of Mars -- Part 4 - Part 5. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Empirical Problem of Determining an Orbit -- "Phase 0": On the Real versus the Mean Sun.; Generally corresponds to the video segment: Class 3, Part 4 - 5.